Agricultural biodiversity in climate change adaptation planning - Bedmar Villanueva, Ana; Halewood, Michael; López Noriega, Isabel (European Center of Sustainable Development, 2017)
Climate change is one of the biggest threats to food production worldwide. Recently, an increasing number of initiatives have embraced the concept of climate smart agriculture to respond to climate change adaptation and mitigation challenges. A central component of this approach is the use of agricultural biodiversity at the genetic, species and ecosystem levels for increasing productivity, adaptability and resilience of agricultural production systems. This paper analyses the extent to which the use of agricultural biodiversity is included in the National Adaptation Programmes of Action (NAPAs) developed by 50 least developed countries to guide their actions in relation to climate adaptation. The results of the analyses indicate that in the majority of the NAPAs, agricultural biodiversity has not been incorporated in a comprehensive manner and that increased efforts can be done at national and international levels for effectively making agricultural biodiversity work for most vulnerable countries’ adaptation to climate change.